RATIONALIZATION OF MOLECULAR DESCRIPTORS OF AURONE ANALOGS TOWARD ANTI-MALARIAL ACTIVITY - Gupta, Arun K.; Singh, Priyanka; Sabarwal, Neetu (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Malaria is a vector-borne infectious disease that is widespread in tropical and subtropical regions. Every year approximately 450 million clinical cases are caused by malaria parasites and 3.2 billion people in the world are living under the risk of malaria. The growing resistance of the parasites to anti-malarial agents is responsible for some of the worst cases in the tropical world. In view of above and as a part of our effort to develop newer anti-malarial agents, molecular modeling analysis was performed to develope QSAR models that show substantial predictive promise for aurones. The QSAR model explains 86.9 percent variance in activity with low standard error of estimation (0.221). Model showed statistical significant internal predictivity (Q2=0.816) and external predictivity (r2pred=0.751) values. The detailed structural investigation revealed that the anti-malarial activity is predominantly explained by the GETAWAY (H6m & R2v) and MoRSE-Code (Mor30v) descriptors. The structural insights gleaned from the study are helpful in design of inhibitors with enhanced potency. Running title: Aurone QSAR analysis Keywords: QSAR; Aurone analogs; Anti-malarial activity; Molecular descriptors